2021
DOI: 10.1016/j.heliyon.2021.e07217
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific determinants of Zai technology use intensity for improved soil water management in the drylands of Upper Eastern Kenya

Abstract: Degraded landscapes and soil water stress are long-standing problems to smallholder agriculture in the drylands. Despite the important roles of zai technology in restoring degraded landscapes and improving agricultural productivity, the technology is yet to be adopted to its fullest extent. This can be attributed to gender-linked disparities in agricultural technology utilization. The study, therefore, sought to determine gender-specific determinants of zai technology choice and use-intensity. A multistage sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 78 publications
2
4
0
Order By: Relevance
“…Similarly, adoption of FISP and ISFM technologies were positively promoted by the size of land (Adolwa et al, 2019; Khonje et al, 2022; Manda et al, 2016; Tesfaye et al, 2020). For adoption intensity, the study is consistent with the conclusion that total land size affected the choice and use intensity of Zai pits (Ndeke et al, 2021). However, the results contradicts the findings of Awuni et al (2018) and Zakaria et al (2020) who reported that farm size negatively influenced adoption of improved agricultural technologies.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, adoption of FISP and ISFM technologies were positively promoted by the size of land (Adolwa et al, 2019; Khonje et al, 2022; Manda et al, 2016; Tesfaye et al, 2020). For adoption intensity, the study is consistent with the conclusion that total land size affected the choice and use intensity of Zai pits (Ndeke et al, 2021). However, the results contradicts the findings of Awuni et al (2018) and Zakaria et al (2020) who reported that farm size negatively influenced adoption of improved agricultural technologies.…”
Section: Resultssupporting
confidence: 87%
“…On the other hand, climate change impacts on the sustainability of food systems threatens the state of food and nutrition security across the globe (Yazar & Ali, 2017). The stress of growing population which is largely disenfranchised and climate variation is more pronounced in sub‐Saharan Africa (SSA) and especially in the dry areas (Mugwe & Otieno, 2021; Ndeke et al, 2021). Vulnerability to climate change variation in SSA has worsened because of high dependence on agriculture, high‐poverty levels, inadequate and poor infrastructure, poor implementation of existing policies and limited access to improved agricultural inputs (Phiiri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of households were male-headed implying that men stood a higher chance to make decisions on which Regenerative Agriculture technologies should be used on their farms. The findings resonate with those of Mwaura et al (2021).This indicates that men were responsible for making major farm/household decisions (Ndeke et al, 2021).Thus households headed by male had higher chances of using compost manure as compared to female-headed households (Usman et al, 2019).This finding is comparable to those of (Ndeke et al, 2021;Sanou et al, 2019;Wekesa et al, 2018) who noted that gender positively affected adoption of new agricultural innovations. In a contrary opinion by (Bessah et al, 2021) , women are most likely to take up new innovations when compared to men to avoid the overarching constraints resulting from extreme weather events that directly affect them than men Marital status negatively and significantly influenced uptake of cover cropping implying that married farmers had lower chances of practicing cover cropping as compared to single farmers.…”
Section: Support Required By Farming Households To Increase Uptake Of...supporting
confidence: 65%
“…Farming experience negatively as well as positively influence the likelihood of taking up agricultural innovations (Zakaria et al, 2020).This could be related with trade-offs that come with technological innovations. As farmers gain more experience in farming, they tend to shift from technologies that yield lower returns to those that are likely to give higher returns (Ndeke et al, 2021).…”
Section: Support Required By Farming Households To Increase Uptake Of...mentioning
confidence: 99%
See 1 more Smart Citation